Winthrop University: School Partnership Network - Johnson, Lisa; Rakestraw, Jennie (Educational (Re)naissance, 2013)
John Goodlad, in his book A Place Called School (1984), suggested that, in order to improve schools and the work of teachers, a relationship had to exist between institutes of public education and teacher preparation programs. Today Goodlad’s message continues to hold significant bearing on whether or not all students receive a high quality, equitable education. The Agenda for Education in a Democracy, formulated by Goodlad and the National Network for Educational Renewal over twenty years ago, promotes simultaneous renewal of P-12 education and educator preparation, advocating equity in schooling and engagement in nurturing pedagogy to meet the diverse needs of students.